2017
DOI: 10.1093/scan/nsx030
|View full text |Cite
|
Sign up to set email alerts
|

An unpleasant emotional state reduces working memory capacity: electrophysiological evidence

Abstract: Emotional states can guide the actions and decisions we make in our everyday life through their influence on cognitive processes such as working memory (WM). We investigated the long-lasting interference that an unpleasant emotional state had on goal-relevant WM representations from an electrophysiological perspective. Participants performed a change detection task that was preceded by the presentation of unpleasant or neutral task-irrelevant pictures in a blocked fashion. We focused on the contralateral delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 75 publications
11
71
1
Order By: Relevance
“…This finding corroborates with the extensive literature that indicates that our ability to perform goal-directed tasks can be disrupted by emotional responses to distractive affective stimuli (Vuilleumier and Schwartz, 2001;Erthal et al, 2005;Dolcos and McCarthy, 2006;Fernandes et al, 2013;Oliveira et al, 2013;Stout et al, 2013). Additionally, Figueira et al (2017) demonstrated that the emotional state effect on WM capacity is influenced by thought control ability traits (Luciano et al, 2005). Individuals who experienced more intrusive thoughts were more susceptible to the effect of the emotional state on WM capacity (Figueira et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding corroborates with the extensive literature that indicates that our ability to perform goal-directed tasks can be disrupted by emotional responses to distractive affective stimuli (Vuilleumier and Schwartz, 2001;Erthal et al, 2005;Dolcos and McCarthy, 2006;Fernandes et al, 2013;Oliveira et al, 2013;Stout et al, 2013). Additionally, Figueira et al (2017) demonstrated that the emotional state effect on WM capacity is influenced by thought control ability traits (Luciano et al, 2005). Individuals who experienced more intrusive thoughts were more susceptible to the effect of the emotional state on WM capacity (Figueira et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
“…Previously, we showed that a negative emotional state (induced by presenting distractive negative pictures) disrupts and reduces WM capacity, which was measured using the electrophysiological index denominated contralateral delay activity (CDA; Figueira et al, 2017). This finding corroborates with the extensive literature that indicates that our ability to perform goal-directed tasks can be disrupted by emotional responses to distractive affective stimuli (Vuilleumier and Schwartz, 2001;Erthal et al, 2005;Dolcos and McCarthy, 2006;Fernandes et al, 2013;Oliveira et al, 2013;Stout et al, 2013).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Emotional state has also been shown to impact the manner in which facial stimuli are processed, with negative emotional states reducing the degree to which faces are processed holistically (Curby, Johnson, & Tyson, ). Further, emotional state has also been shown to modulate memory recall and information processing style more generally, with evidence, across studies, that different mood states can both reduce (e.g., Figueira et al ., ) or enhance working memory performance depending on the valence of the mood state (e.g., Storbeck & Maswood, ). These previous studies suggest that positive and negative mood measures could be insightful for understanding the VWM cost we found for fearful faces.…”
Section: Methodsmentioning
confidence: 99%
“…A pivotal role among these conditions is assigned to working memory capacity (WMC; Baddeley, 1992;Dehaene, 2014). Situational factors, such as fatigue, alcohol intoxication, unpleasant emotional state (Figueira et al, 2017), and anxiety (Moran, 2016), impede the functioning of working memory. Individual differences in WMC are found to be significantly related but not identical to both crystallized and fluid intelligence (for a meta-analysis, see Ackerman, Beier, & Boyle, 2005).…”
mentioning
confidence: 99%